Pattern & Management of Mandible Fracture in the Department of Maxillofacial Casualty Dhaka Dental College & Hospital: A Retro- spective Cross Sectional Study of 435 Patients - Sultana, Farjana; Karim, Md Rezaul; Bhuiyan, Rafiq Ahmed; Lita, Ismat Ara Haider (Update Dental College Journal, 2018)
The retrospective cross sectional study was undertaken to determine the pattern and different meth- ods of treatment of mandible fractures. Four hundred and thirty five patients with mandibular fractures were treated during the year 2014-2015. Among the patients attended with facial trauma during men- tioned period at casualty department of Dhaka Dental College hospital with the mandible fracture not associated with others facial bone fracture who were managed in this department and whose clinical record file are available in our record book were included in this study. A review of patients’ records and radiographs was conducted. Data regarding age, gender, cause of fracture, anatomic site and treatment modalities were reviewed. Data were presented by table and diagram. Age, location of fracture in table form, gender distribution, treatment in pie chart, etiology of fracture by histogram. There was higher prevalence in male (3.9:1), with occurrence peak between 21-30 years. The princi- pal causes of fracture in this study were RTA (Road Traffic Accidents) representing 54.02 %( n=235), followed by physical assault 17.24% (n=75), Fall, Sports injury, Blow by heavy objects, Tube well injury & others. The most injured sites were in decreasing order parasymphysis (26.31%) followed by angle of mandible 17.89% then symphysis, condyle, body of mandible dentoalveolar, ramus, coronoid process of mandible. Most patients of mandibular fractures were treated by closed reduction (arch bar, arch bars with intermaxillary fixation IMF,eyelet wiring& lateral compression plate). Rest of the patients were treated with open reduction ( miniplates fixation. 3D plate fixation) .Only 8.05% patients were managed by conservative approach. This study reflects patterns of mandibular fracture within the community and discuuss various methods of mandible fracture management in the department of Maxillofacial casualty in Dhaka Dental college hospital. It is hoped that assessment presented here will be valuable to government agencies and health care professionals involved in planning future programs of prevention & treatment of mandible fracture. Update Dent. Coll. j: 2018; 8 (1): 11-16